Conducting Robust Intervention Trials to Address the Sensory Needs of Children with Autism Spectrum Disorder: Design Challenges in an Australian Context. (October 2014) - Weeks, Scott; Grimmer, Karen; Boshoff, Kobie; Stewart, Hugh
Many occupational therapists administer sensory interventions to address the needs of children with autism spectrum disorder. However, the current evidence regarding the effectiveness of sensory interventions is inconclusive, resulting in calls for more robust testing through randomized controlled trials. Our initial research plan was to conduct a randomized controlled trial that had real-world applications for occupational therapists and children diagnosed with autism spectrum disorder. However, as we conceptualized this study, we identified many uncertainties regarding the criteria required for a robust trial. In this opinion piece we describe and discuss the challenges we encountered when designing a community-clinic-based effectiveness study in an Australian context.